Increasing Motivation to Learn Volleyball Games by Warming Up the Game (Kasti Ball) in Grade IV Students at SDN Jumblang, Kandangan District - Andik Hermawan (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2023)
This research started with the findings of experts and observers of sports and health physical education (Penjasorkes) who concluded that the learning process in Penjasorkes was still not effective, so someone needed to improve their abilities, one of which was by conducting Classroom Action Research. Data collection techniques used are: observation, interviews and documentation. This research was conducted at SDN Jlumbang, Kandangan District, Kediri Regency. Data collection uses a learning system with 3 cycles. In addition to collecting data, researchers also use a questionnaire as an instrument. Through the analysis of each learning cycle, data was obtained showing that in the first cycle of learning (learning without using small ball games in the warm-up) as many as 11 students (48%) were motivated by Physical Education subjects. While in the second cycle of learning (learning using small ball games during the warm-up) as many as 15 students (65%) students were motivated while in the third cycle (learning using small ball games in the warm-up) as many as 20 students (87%). This shows that there is an increase in motivation after learning using small ball games, so that students feel motivated in doing learning